2016
DOI: 10.1017/s1751731116000513
|View full text |Cite
|
Sign up to set email alerts
|

Modification of abomasum contractility by flavonoids present in ruminants diet: in vitro study

Abstract: Flavonoid supplementation is likely to be beneficial in improving rumen fermentation and in reducing the incidence of rumen acidosis and bloat. Flavonoids are also said to increase the metabolic performance during the peripartum period. Ruminants are constantly exposed to flavonoids present in feed. However, it is not clear if these phytochemicals can affect the activity of the gut smooth muscle. Therefore, the aim of the study was to verify the effect of three flavonoids on bovine isolated abomasum smooth mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Preparations with chamomile were used as an infusion mainly to treat diarrhoea in calves. Chamomile flavonoids showed spasmolytic effects on bovine intestinal smooth muscles (Mendel et al, 2016). Chamomile also exhibited in vitro antibacterial properties against pathogens relevant in gastrointestinal disorders of youngstock (Ayrle et al, 2016a).…”
Section: Chamomile Flowers (Matricaria Chamomilla L Matricariae Flos)mentioning
confidence: 97%
“…Preparations with chamomile were used as an infusion mainly to treat diarrhoea in calves. Chamomile flavonoids showed spasmolytic effects on bovine intestinal smooth muscles (Mendel et al, 2016). Chamomile also exhibited in vitro antibacterial properties against pathogens relevant in gastrointestinal disorders of youngstock (Ayrle et al, 2016a).…”
Section: Chamomile Flowers (Matricaria Chamomilla L Matricariae Flos)mentioning
confidence: 97%
“…The predominant influence of PSM on final type and size of interactions can be explained by their nonspecific mechanism of action on gastrointestinal smooth muscles. As proposed before, both flavonoids and saponins interfere with the structure of smooth muscle cell membranes, change their permeability and depolarization status and consequently reactivity to other agents (Ma & Xiao, ; Dar & Channa, ; Mendel et al., , ). The nonspecific effect of the tested phytocompounds on gut smooth muscle explains the ability to change strips’ response to pharmaceutical agents of different modes of action.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, the study herein was focused on the interactions of PSM in nonsugar form with pharmaceutical agents. Our previous findings indicated that apigenin and quercetin as well as hederagenin and medicagenic acid significantly affect the contractility of bovine abomasum and duodenum smooth muscle (Mendel et al., , ). Therefore, we hypothesized that all of previously tested PSM might be able to modify the effect of pharmaceutical agents which are known to affect gastrointestinal motoric activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They all contain high concentrations of crude protein, and easily degradable carbohydrates, but are rather low in phytochemicals. It is not unlikely that with the narrow botanical and biochemical spectrum of these intensive diets important functions of phytochemicals for rumen control (Buccioni, Decandia, Minieri, Molle, & Cabiddu, 2012;Cobellis et al, 2016;Mendel, Chlopecka, Dziekan, & Karlik, 2016), lipid metabolism (Khiaosa-ard et al, 2009;Leiber, Willems, Werne, Ammer, & Kreuzer, 2019), antioxidative protection, immune factors and hormone regulation (Oh et al, 2017) have been lost. The implications of this loss for animal health are not yet sufficiently understood.…”
Section: Introductionmentioning
confidence: 99%